Converging paths: Green Chemistry and Human Rights Advocacy - Justino, E.; Belchior-Rocha, H. (4th Edition of International Conference on Green Chemistry and Renewable Energy, 2024)
This presentation explores the interconnected discourses of green chemistry and human rights advocacy, highlighting their shared objectives and synergistic potential. Green chemistry, as a discipline, emphasizes the design of chemical products and processes that reduce or eliminate hazardous substances, minimize waste, and conserve resources, thereby promoting environmental sustainability. Conversely, human rights advocacy focuses on protecting and promoting the inherent dignity and rights of all individuals, encompassing principles of equity, justice, and access to essential resources. The relation between green chemistry and human rights advocacy arises from their mutual pursuit of a healthier, safer, and more equitable world.